Bonding Performance on Steel Bar in Concrete Containing Expanded Polystyrene (EPS) and Palm Oil Fuel Ash (POFA) by Pull Out Test with 0.6% of Water to Cement Ratio - NIZAM BIN GURIMAN, MOHAMMAD RAHMAT AYRAN; Hairi Osman (Progress in Engineering Application and Technology, 2024)
This study explored the bond performance between Palm Oil Fuel Ash (POFA), Expanded Polystyrene Styrofoam (EPS), and steel reinforcement in concrete. This research aimed to solve concrete bonding issues with POFA and EPS and to reduce the environmental footprint of the construction industry, promote alternative materials and improve the performance of concrete structures. Concrete samples were tested with compression tests, tension tests and pull-out tests to achieve the objective of the study. Testing 20 MPa grade concrete containing POFA replacing cement at 0%, 10%, and 20%, and partial fine aggregate replacement with EPS at 0% and 10%, showed a decrease in compressive strength with higher POFA and EPS replacement. Treatment of POFA (T-POFA) was carried out to test whether the strength of concrete could be improved from Untreated POFA (U-POFA). Treated POFA (T-POFA) shows improved chemical properties, especially improving the bond between EPS and cement, increasing the pull-out strength. Recommendations suggest limiting POFA replacement to 10% while the EPS should not replace more than 10% and exploring treatment methods to optimize concrete strength.